CULINARY MAPPING IN SEMARANG CITY (CHINESE MENU) - Dewi Maria, Aletta; Kholil Aswan, Mukhamad; Mansur, Ahmad; Mulyoko, Mulyoko; Ray Octafian (Brilliant International Journal Of Management And Tourism, 2022)
The general objective of this study was to determine the culinary mapping of Peranakan Chinese menu in Semarang City, Central Java. The specific objectives of this research are to find out how to provide Peranakan Chinese menu culinary based on the number and types that exist in Semarang City. Furthermore, to find out how to serve the Peranakan Chinese menu culinary provision and to find out efforts to preserve the Peranakan Chinese menu as a culinary speciality of Semarang City. The technique of collecting primary data is very useful for collecting information needed for analysis and decision making. Based on the results of the research, it is obtained that the provision of Peranakan Chinese menu culinary in the city of Semarang in several types of dishes and drinks still uses original recipes from ancestors, both cooking ingredients, spices and cooking techniques. The culinary presentation of the Peranakan Chinese menu in some culinary shows distinctiveness without leaving its authenticity even though there are several additional menu variants. Efforts to preserve the Peranakan Chinese menu as a culinary speciality of the city of Semarang have been made by culinary business people, families, communities and the Semarang City government.